Constructing Hierarchically Hollow Core–Shell MnO2/C Hybrid Spheres for High‐Performance Lithium Storage. Issue 29 (8th June 2016) - Wang, Gang; Sun, Yuhan; Li, Debao; Wei, Wei; Feng, Xinliang; Müllen, Klaus
Abstract : Hierarchical MnO2 /C hybrid spheres (MCS@MnO2 ), consisting of numerous hollow core–shell MnO2 @C nanospheres, are developed via a facile deposition process. The well‐defined inner voids and robust carbon framework endow MCS@MnO2 with excellent mechanical stability, efficient utilization of MnO2, and enhanced reaction kinetics for Li‐ion batteries, therefore leading to large specific capacities, superior rate capability, and long‐term cycling stability.